The Implementation of Integrated Health Information Systems – Research Studies from 7 Countries Involving the InterRAI Assessment System - de Almeida Mello, Johanna; Wellens, Nathalie IH; Hermans, Kirsten; De Stampa, Matthieu; Cerase, Valérie; Vereker, Natalie; Jónsson, Pálmi V.; Finne-Soveri, Harriet; Meehan, Brigette; Declercq, Anja (International Journal of Integrated Care, 2023)
Introduction: In the past years, governments from several countries have shown interest in implementing integrated health information systems. The interRAI Suite of instruments fits this concept, as it is a set of standardised, evidence-based assessments, which have been validated for different care settings. The system allows the electronic transfer of information across care settings, enabling integration of care and providing support for care planning and quality monitoring. The main purpose of this research is to describe the recent implementation process of the interRAI instruments in seven countries: Belgium, Switzerland, France, Ireland, Iceland, Finland and New Zealand.Methods: The study applied a case study methodology with the focus on the implementation strategies in each country. Principal investigators gathered relevant information from multiple sources and summarised it according to specific aspects of the implementation process, comparing them across countries. The main implementation aspects are described, as well as the main advantages and barriers perceived by the users.Results: The seven case studies showed that adequate staffing, appropriate information technology, availability of hardware, professional collaboration and continuous training are perceived as important factors which can contribute to the implementation of the interRAI instruments. In addition, the use of electronic standardised assessment instruments such as the interRAI Suite provided evidence to improve decision-making and quality of care, enabling resource planning and benchmarking.Conclusion: In practice, the implementation of health information systems is a process that requires a cultural shift of policymakers and professional caregivers at all levels of health policy and service delivery. Information about the implementation process of the interRAI Suite in different countries can help investigators and policymakers to better plan this implementation. This research sheds light on the advantages and pitfalls of the ...